Antonie van Leeuwenhoek Journal of Microbiology - Dunlap, Christopher; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
This journal publishes papers on fundamental and applied aspects of microbiology, with a particular emphasis on the natural world. Topics covered range from molecular biology and genetics to ecology and marine microbiology, as well microbial pathogenesis and bioinformatics. These can be in applied contexts such as agriculture, food microbiology and assay development amongst others. New taxa descriptions must demonstrate scientific interest beyond minimum description requirements to warrant consideration. Ideally, new taxa descriptions should part of a broader scientific study, rather than a short note format. Authors submitting biotechnological manuscripts should consider whether their work is better suited to a more specialised biotechnology journal. Likewise, authors submitting medical microbiology manuscripts papers should consider whether their work is better suited to a more specialised medical microbiology journal.
Keywords: Medical microbiology; Microbiology; Plant science; Botany; Soil science; Soil conservation; Microbiology; Medical Microbiology; Plant Sciences; Soil Science & Conservation